Clinical Imaging Findings of Vestibular Aqueduct Trauma in a Patient With Posttraumatic Meniere's Syndrome - Bächinger, David; Goosmann, Madeline M.; Schuknecht, Bernhard; Nadol, Joseph B.; Adams, Joe C.; Huber, Alexander; Eckhard, Andreas H. (Frontiers in Neurology, 2019)
Posttraumatic Meniere’s syndrome is a rare clinical entity. The pathomechanism by which temporal bone trauma leads to fluctuating audiovestibular symptoms, in some cases with a delay of onset many years after trauma, remains elusive. Here, a clinical case and the respective temporal bone imaging data were reviewed to investigate the underlying inner ear pathology. A 44-year-old patient presented with left-sided Meniere’s syndrome 34 years after he suffered an ipsilateral temporal bone fracture caused by a car accident. Clinical imaging showed left cochleovestibular hydrops (gadolinium-enhanced MRI) and bony obliteration of the left VA (CT imaging), resulting in discontinuity of the ES. Our findings suggest that a temporal bone fracture with a “retrolabyrinthine” course, traversing the VA, caused intraaqueductal callus bone formation and progressive blockage of the VA. As a result, the extraosseous (distal) endolymphatic sac (eES) became separated from the cochleovestibular labyrinth, an event that presumably underlies endolymphatic hydrops formation and that precipitates the onset of clinical Meniere’s symptoms in this case.